Longitudinal assessment of young swimmers` performance and its predictors - Morais, J.; Silva, A.; Marinho, D.; Lopes, V.; Morouço, P.; Barbosa, T. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study was to develop a performance predictor model based on biomechanics. Ninety-one swimmers (44 boys and 47 girls) were evaluated. The decimal age, anthropometrics, kinematics and efficiency parameters were collected in ten different moments over three seasons. Hierarchical linear modeling was the procedure selected to estimate the performance predictors. The decimal age (Estimate: -2.05; P < 0.001), arm span (Estimate: -0.59; P < 0.001), stroke length (Estimate: 3.82; P = 0.002) and propelling efficiency (Estimate: -0.17; P = 0.001) entered the final model. The decimal age, arm span, stroke length and propelling efficiency were the main predictors. Longitudinal assessments seems to be the best way to have a deeper knowledge on how performance main determinants act and affect the performance.